Perangkap Agama dan Etnik: Melatarbelakangi Niat Memilih Pemilih Milenial: Religion and Ethnicity Traps: Behind the Intention to Vote of Millennial Voters - Jhon Retei Alfri Sandi (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2021)
Millennial voters are a potential community that is a strategic target for pairs of candidates for regional election contestation to reap the coffers of votes. The campaign approach using religious and ethnic sentiments is an alternative strategy. This study looks at religion and ethnicity influencing millennial voters’ voting intentions. The research method uses quantitative methods with multiple linear regression. The research sample was drawn randomly according to the criteria so that the answers to 280 respondents were analyzed. The study results found that religion significantly influenced millennial voter intentions, while ethnicity did not affect millennial voter intentions. Millennial voters tend not to be interested in practical politics.